Factors Influencing the Adoption of Healthy Lifestyles Among Indonesian Urban Residents - Uktuvia, Anik (Jurnal Health Sains, 2025)
This research investigates the factors influencing the adoption of healthy lifestyles among urban residents in Indonesia, a country experiencing rapid urbanization. The study addresses the rising challenges associated with physical inactivity, poor dietary habits, and obesity, which are increasingly prevalent in urban areas. Using a socio-ecological model, the research explores how individual, social, and environmental factors contribute to healthy lifestyle adoption. A cross-sectional survey was conducted across major Indonesian cities, with a sample size of 400 respondents. The findings reveal that autonomous motivation and social support significantly influence lifestyle behaviors, while environmental factors such as neighborhood walkability also play a crucial role. However, barriers such as unhealthy retail exposure and time constraints hinder the adoption of healthy behaviors. The study suggests that integrated interventions targeting both individual motivation and urban infrastructure, including improved walkability and healthier food environments, are necessary to promote healthy lifestyles. This research contributes to the socio-ecological framework by incorporating specific urban factors, providing actionable insights for policymakers and urban planners to enhance public health.